(untitled) (Texas Journal of Multidisciplinary Studies, 2023)
This article is devoted to the study of the characteristics of the monograph genre, which is the most common type of scientific style. The fact that the monograph is a genre of pure scientific style, its linguistic aspects, compositional structure, and its role in scientific communication are discussed